2018
DOI: 10.1007/s10902-018-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Lay Theories for Life Satisfaction and the Belief that Life Gets Better and Better

Abstract: Many individuals believe that life gets better and better over time. To examine the sources and significance of such beliefs, we examined lay theories for life satisfaction (LS) in relation to individuals' beliefs concerning how their LS was unfolding over time. Two studies were conducted with online participants: one correlational (Study 1; N = 320, M age = 30.39, 55% male), the other experimental (Study 2; N = 321, M age = 30.46, 53% male). In both studies more incremental (vs. entity) lay theories were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…To address these concerns, we searched the literature through PubMed, Web of Science, and Google Scholar databases for studies with the following criteria: 1) assessing subjective wellbeing with the Cantril Ladder and 2) among participants from an MTurk population. Two studies met those criteria (Busseri & Samani, 2018;Whillans et al, 2017). The study of Busseri and Samani (2018) investigated lay theories for life satisfaction and reported the following Ladder scores in two MTurk samples: Study 1, N=320, 5.98 (SD=2.27); Study 2, N=321, 6.09 (SD=2.15).…”
Section: Reanalysis Of a Previously Published Studymentioning
confidence: 99%
See 2 more Smart Citations
“…To address these concerns, we searched the literature through PubMed, Web of Science, and Google Scholar databases for studies with the following criteria: 1) assessing subjective wellbeing with the Cantril Ladder and 2) among participants from an MTurk population. Two studies met those criteria (Busseri & Samani, 2018;Whillans et al, 2017). The study of Busseri and Samani (2018) investigated lay theories for life satisfaction and reported the following Ladder scores in two MTurk samples: Study 1, N=320, 5.98 (SD=2.27); Study 2, N=321, 6.09 (SD=2.15).…”
Section: Reanalysis Of a Previously Published Studymentioning
confidence: 99%
“…Two studies met those criteria (Busseri & Samani, 2018;Whillans et al, 2017). The study of Busseri and Samani (2018) investigated lay theories for life satisfaction and reported the following Ladder scores in two MTurk samples: Study 1, N=320, 5.98 (SD=2.27); Study 2, N=321, 6.09 (SD=2.15). Those scores are higher than the scores of our MTurk sample, but lower than the scores observed in the UAS and Gallup samples.…”
Section: Reanalysis Of a Previously Published Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also identified important implications of holding such beliefs. Greater (vs. lesser) perceived improvement from one's recollected past to current LS is linked with various indicators of adaptive functioning, including more positive mental, physical, and interpersonal functioning (Busseri et al, 2009a(Busseri et al, , 2009b(Busseri et al, , 2012Busseri & Merrick, 2016;Busseri & Peck, 2015;Choma et al, 2014); and more effective self-regulation and goal pursuit (Busseri & Samani, 2019;Conway, 2005;Sutin & Robins, 2008). Such findings are consistent with temporal self-appraisal theory (Wilson & Ross, 2001; see also, Peetz & Wilson, 2008), according to which individuals are willing to derogate their past selves in order to enhance (or maintain) their current self-regard.…”
Section: Life Satisfaction and The Belief That Life Gets Better And Bettermentioning
confidence: 99%
“…Participants' general motivation for the future and their perceived likelihood of achieving specific future plans were measured separately (following measures employed by Busseri & Samani, 2019).…”
Section: Motivationmentioning
confidence: 99%